Perawatan Diri pada Orang dengan Gangguan Jiwa (ODGJ) di Pusat Rehabilitasi Narkoba dan Gangguan Jiwa Kabupaten Banyuasin - Pastari, Marta; Endriyani, Sri; Martini, Sri (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2023)
Abstract The Mitra Mulia Foundation is a Social and Independent Drug and Mental Disorder Rehabilitation Center located on Jalan Talang Buluh Dusun I RT.02 Kel. Talang Buluh, Kec. Talang Kelapa Kab. Banyuasin which is about 10 KM from the city center. Based on a preliminary study and permission to carry out activities carried out by the service team in May 2022, the problem was found; There is no self-care activity independently in the daily schedule of patients with hallucinations and as many as 10 out of 38 patients with hallucinations (26.3%) experience self-care deficits as evident from the inability to take care of personal hygiene, eat independently, decorate independently and toileting (defecation / urination). The solutions offered include; Education and accompaniment (Personal Hygiene Occupational Group Activity Therapy) for ODGJ with Hallucinations and Management at the Mitra Mulia Foundation as well as Redemonstration and Assistance (Personal Hygiene Occupational Activity Therapy) which was given to 10 patients with hallucinations (5 people/group) and 9 people managing the Mitra Mulia Foundation which was carried out during July-September 2022. Based on the achievement targets and results of activities, it can be concluded that; ODGJ with Hallucinations already has a routine activity schedule and includes self-care activities independently into the daily schedule; Reducing the incidence of self-care deficits in ODGJ with Hallucinations